Effect of the number of blades in palm oil chopping machine - Fajar David Aminuddin; Anis Siti Nurrohkayati; Muhammad Ali Rohmatulloh (LPPMPK- Universitas Muhammadiyah Cileungsi, 2024)
A single hectare of oil palms may yield 10 tons of fronds annually, with young oil palms producing 40–56 fronds and mature oil palms producing 40–48 fronds. One kind of solid debris that comes from making palm oil is called palm oil fronds. A method is required to lessen palm frond waste because substantial volumes of it will still need to degrade. Waste palm fronds are reduced in size and broken down more quickly with the assistance of a chopping machine. But for slicing palm frond trash, the frond machines that are now in use are not the best. The purpose of this study is to ascertain whether adding more blades to a chopping machine's cutting knife can enhance the chopping process. Two designs with 19 and 26 blades were manufactured and tested for the research, and the results were compared with the cutting knife design from the prior study, which had 24 blades. According to the test results, adding additional blades to the cutting knife will improve the machine's effective capacity by 14.22% and decrease the size of waste palm fronds and leaves, allowing the machine to operate more efficiently. In addition, reducing the size of palm fronds with more knives can make them easier to break down